Infants Born to Mothers with Clinical Chorioamnionitis: A Cross-Sectional Survey on the Use of Early-Onset Sepsis Risk Calculator and Prolonged Use of Antibiotics - Ayrapetyan, Marina; Carola, David; Lakshminrusimha, Satyan; Bhandari, Vineet; Aghai, Zubair H. (American Journal of Perinatology, 2019)
Objective To evaluate variations in practice for the management of neonates born to mothers with clinical chorioamnionitis.Methods This was a prospective cross-sectional survey consisting of 10 multiple choice questionnaires distributed to 2,900 members of the Perinatal Section of American Academy of Pediatrics. Variations in responses were assessed and compared between the various groups.Results A total of 682 members (23.5%) completed the survey; 169 (24.8%) indicated that they use the neonatal early-onset sepsis (EOS) risk calculator for the management of neonates born to mothers with clinical chorioamnionitis. More respondents from the western region of United States and level III units are using the EOS risk calculator compared with the south and level II units. Approximately 44% of the respondents indicated that they will not stop antibiotics at 48 to 72 hours in asymptomatic neonates born to mothers with chorioamnionitis with negative blood culture if the complete blood count (CBC) and C-reactive protein (CRP) are abnormal.Conclusion A large number of practitioners are using the neonatal EOS risk calculator for neonates born to mothers with chorioamnionitis. Despite a clear guideline from the Committee on Fetus and Newborn, almost 44% will treat healthy-appearing neonates born to mothers with chorioamnionitis with a prolonged course of antibiotics solely for abnormal CBC or CRP.
Keywords: sepsis; neonates; EOS calculator; maternal fever